Upaya Pelestarian Bahasa Daerah Melalui Ketoprak Madura (Ludruk) : Kajian Sosiolingustik - Olivia Ananda; Abelia Nur Hikmah; Iwan Firdaus (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study uses a qualitative research method, which is a research approach that focuses on an in-depth understanding of a phenomenon or something. This article aims to find out how the preservation of the Madurese language is through the art of Ketoprak Madura (Ludruk), such as from its songs and from its speech. Ketoprak Madura (Ludruk) functions not only as entertainment, but can also be used as a medium for preserving the Madurese language. Therefore, it will be very important to instill a sense of love for the Madurese language so that it remains preserved, considering that currently the Madurese language has experienced many shifts in use, especially for the younger generation who currently use more Indonesian than Madurese itself.